Novel Antibiotic Resistance Mechanisms in Clinical Bacteria: Implications for Treatment Strategies - Redha, Malak Radwan Abdul; Abed, Hawraa Riyadh; Hammood, Nada Hussein; mahde, Ahmed abdulhakeem; Kazim, Asawr Jasim (American Journal of Biology and Natural Sciences, 2024)
The past few decades have seen the rapid emergence and spread of bacteria that are resistant to multiple antibiotics. This increased level of resistance has resulted in a number of challenges when it comes to treating infections in the clinic, and healthcare providers are finding themselves with limited options for treatment.